Improvement of 2000-m rowing performance with caffeinated carbohydrate-gel ingestion - Scott, A. T.; O`Leary, T.; Walker, S.; Owen, R. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate the effect of ingesting a caffeinated carbohydrate gel (CC) 10 minutes prior on 2000-m rowing performance compared with a carbohydrate-only placebo gel (CP). Methods: A counterbalanced, single-blind, crossover study design was employed (N = 13). All participants completed 1 familiarization trial followed by 2 experimental rowing time trials. The experimental trials were performed 10 min after ingesting CP (21.6 g of carbohydrate, 0 mg caffeine) or CC (21.6 g carbohydrate, 100 mg caffeine), and heart rate (HR), oxygen consumption (VO2), carbon dioxide production, minute ventilation (VE), respiratory-exchange ratio (RER), rating of perceived exertion (RPE), gastrointestinal discomfort (GI), and thirst perception (Thirst) were recorded every 200 m. Blood lactate [La-] was recorded immediately before and after exercise. Results: A pairedsamples t test identified a significant improvement in 2000-m performance of 5.2 ± 3.9 s (1.1% ± 1.7%; P = .034). Two-way repeated-measures ANOVA revealed no significant treatment effect for HR (177 ± 8 vs 177 ± 9 beats/min, P = .817), VO2 (46.1 ± 6.5 vs 46.6 ± 6.2 mL/kg·min, P = .590), VE (121.8 ± 14.7 vs 124.8 ± 15.7 L/min, P = .490), RPE, GI, or Thirst for CP and CC, respectively. Paired-samples t tests revealed no treatment effect for postexercise [La-] between CP and CC (11.72 ± 2.69 vs 12.26 ± 3.13 mmol/L, P = .534). Conclusion: A relatively low dose of caffeine (1.3 ± 0.1 mg/kg body mass) in an isotonic carbohydrate gel ingested only 10 min before performance improved 2000-m rowing time by 5.2 ± 7.8 s (1.1% ± 1.7%).